2020
DOI: 10.3390/molecules25174020
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Differential Antioxidant Activity of Maslinic Acid in Murine Melanoma Cells and in Rat Embryonic Healthy Cells Following Treatment with Hydrogen Peroxide

Abstract: Maslinic acid (MA) is a natural triterpene from Olea europaea L. with multiple biological properties. The aim of the present study was to examine MA’s effect on cell viability (by the MTT assay), reactive oxygen species (ROS levels, by flow cytometry) and key antioxidant enzyme activities (by spectrophotometry) in murine skin melanoma (B16F10) cells compared to those on healthy cells (A10). MA induced cytotoxic effects in cancer cells (IC50 42 µM), whereas no effect was found in A10 cells treated with MA (up t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…MA showed significant cytotoxicity in B16F10 cells with an IC 50 value of 42 µM, but no obvious toxicity for A10 cells at concentrations up to 210 µM. 50 …”
Section: Anticancer Properties Of Maslinic Acidmentioning
confidence: 88%
“…MA showed significant cytotoxicity in B16F10 cells with an IC 50 value of 42 µM, but no obvious toxicity for A10 cells at concentrations up to 210 µM. 50 …”
Section: Anticancer Properties Of Maslinic Acidmentioning
confidence: 88%
“…For this reason, the role of changes in the cellular concentration of reducing equivalents in the form of NADPH is vital. In fact, molecules of this reduced coenzyme play fundamental roles in controlling ROS levels and in numerous metabolic processes involved in cell growth and development: they serve as a connection between anabolic and catabolic processes [ 15 , 16 ], are key in maintaining the redox balance [ 12 , 17 , 18 ], actively participate in the detoxification processes [ 19 ], contribute to the maintenance of cellular integrity [ 18 , 19 ] and play an active role in cellular and organic aging [ 20 ]. The cellular levels of this reduced coenzyme depend on the enzymatic activity of different NADPH production systems, especially those belonging to the pentose phosphate pathway, G6PDH and 6PGDH, and NADP-dependent isocitrate dehydrogenase (NADP-ICDH).…”
Section: Introductionmentioning
confidence: 99%
“…Among all these phytochemicals, several should be highlighted, namely, terpenoids and polyphenols, of which consequential research related to their bioactive capacities both in vitro and in vivo is being carried out [ 5 ]. Many of these compounds have properties such as anticancer, using different cancer lines, both solid and liquid [ 6 , 7 , 8 , 9 , 10 , 11 ], antiangiogenic [ 7 , 12 , 13 , 14 , 15 ], antioxidant [ 16 , 17 , 18 ], anti-inflammatory [ 19 , 20 ], cardio- and neuroprotective [ 21 , 22 ], antidiabetogenic [ 23 , 24 ], antifungal [ 25 ], antimicrobial and antiviral [ 26 , 27 ], antiparasitic [ 28 ], growth inducing [ 29 , 30 , 31 ], and enzyme inhibitory or activating [ 32 , 33 ], as well as modulators in the production of reducing equivalents whose role is essential to explain most of the processes of metabolic biosynthesis [ 34 ], of cellular and organic growth, nutrition and differentiation processes [ 35 , 36 , 37 , 38 ] as well as, of cellular detoxification processes [ 39 ] and oxygen-free radical scavenging [ 18 , 40 ].…”
mentioning
confidence: 99%
“…Among the active compounds present in the fruit and leaf of the olive tree ( Olea europaea L.), the pentacyclic triterpenes stand out, along with, mainly due to their content, maslinic acid, of which a large number of beneficial health effects have been demonstrated on many occasions [ 5 , 8 , 9 , 10 , 16 , 29 , 30 , 31 , 32 ]. One of the most controversial functions of maslinic acid is its antioxidant capacity; thus, Mokhtari et al [ 18 ] investigated this property in murine cutaneous melanoma cells (B16F10). In addition to the known selective cytotoxic effects of maslinic acid on cancer cells, it was also demonstrated that after provoking an oxidative stress situation by the addition of hydrogen peroxide (H 2 O 2 ), the triterpene isolated from the olive tree protected tumor cells from concomitant oxidative damage by decreasing ROS levels and modifying the activities of different antioxidant enzymes such as superoxide dismutase (SOD), glutathione S-transferase (GST), and glutathione peroxidase (GPX), thus demonstrating a high antioxidant capacity of this triterpene and therefore its beneficial effects on health.…”
mentioning
confidence: 99%